O PÚBLICO E PRIVADO NA POLÍTICA DE SAÚDE: reflexões da publicização da gestão de serviços de assistência médico-hospitalar do Hospital Dr. Carlos Macieira no período de 1997 a 2006 em São Luís/MA - Pessoa, Maria Anadete Abreu (2014)
This study deals with the process of democratization of the Hospital Carlos Macieira (HCM) and its reverberations in hospital medical care provided to public servants of the state of Maranhão. We analyze the characteristics of the so-called New Public Management in Brazil and the changes that occurred in the process of organizing the management of the Hospital Carlos Macieira, as well as the process that was funded by the National Program for Publicization (PNP) and consists of the transfer of enforcement social policies, inserted in calling "nonstate public" sector. Draw up its features and contours in the management of Pro-Health. We analyze these measures as part of the reform of the Brazilian state apparatus that extends up to Maranhão and the other states of the federation as a solution to fiscal crisis announced by the Federal Government in the 1990s.